Design And Implementation of an Object-Following System by Using DJI Tello Drone - Lam Shu Xuan; Aminurrashid Noordin; Suziana Ahmad; Azhan AB Rahman; Mohd Ariffanan Mohd Basri; Izzuddin Mat Lazim; Mustafa Saad Khalifa (Penerbit Universiti Teknikal Malaysia Melaka, 2026)
Indexed by MyCite